2019
DOI: 10.1093/gigascience/giz115
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequence of Solanum aethiopicum provides insights into disease resistance, drought tolerance, and the evolution of the genome

Abstract: Background The African eggplant (Solanum aethiopicum) is a nutritious traditional vegetable used in many African countries, including Uganda and Nigeria. It is thought to have been domesticated in Africa from its wild relative, Solanum anguivi. S. aethiopicum has been routinely used as a source of disease resistance genes for several Solanaceae crops, including Solanum melongena. A lack of genomic resources has meant that breeding of S. aethiopicum has lagged behind other vegetable crops. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 93 publications
(128 reference statements)
0
30
0
Order By: Relevance
“…In addition to wild relatives, crop landraces are a great source of genetic variability for their adaptation to specific ecosystems and climatic conditions (Cantalapiedra et al, 2017;Carvalho et al, 2017;Sani et al, 2018). On the other hand, latest studies with orphan crops have demonstrated that those crops are a powerful tool to improve their related global-traded crops due to its resistance against unfavorable conditions (Song et al, 2019;Tadele and Bartels, 2019).…”
Section: Challenges and Future Solutionsmentioning
confidence: 99%
“…In addition to wild relatives, crop landraces are a great source of genetic variability for their adaptation to specific ecosystems and climatic conditions (Cantalapiedra et al, 2017;Carvalho et al, 2017;Sani et al, 2018). On the other hand, latest studies with orphan crops have demonstrated that those crops are a powerful tool to improve their related global-traded crops due to its resistance against unfavorable conditions (Song et al, 2019;Tadele and Bartels, 2019).…”
Section: Challenges and Future Solutionsmentioning
confidence: 99%
“…melongenae (Rizza et al 2002;Toppino et al 2008) in brinjal eggplant was introduced from the African eggplant, while resistance to late blight (Phytophthora infestans) in potato (Solanum tuberosum) has been traditionally managed through the introgression of major genes from underutilized relatives (Ross 1986;Gebhardt and Valkonen 2001;Van Der Vossen et al 2003;Ghislain et al 2019). A recent whole genome analysis confirmed the abundance of disease resistance genes in the African eggplant (Song et al 2019), making it a great resource for future introgression and R gene cloning. The African rice (Oryza glaberrima Steud.…”
Section: Identification Of Climate Smart Genes In Orphan Crops For Usmentioning
confidence: 99%
“…The use of molecular markers within the African eggplant has been mainly for germplasm or genome characterization (Sakata et al 1991 ; Sakata and Lester 1994 ; Gramazio et al 2016 ; Song et al 2019 ). There is currently no association or linkage mapping studies reported in the literature despite the recent availability of a reference genome (Song et al 2019 ).…”
Section: Genetics and Breeding Of Select Climate Smart Orphan Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assembly was performed using a pipeline containing several softwares (Velvet 28 , SPAdes 29 and SOAP Denovo 30 ) and trimmed (MiSeq and Trimmomatic 31 softwares) or untrimmed data (only MiSeq software). GapCloser software 32 was used to reduce assembly gaps. Scaffolds < 800 base pairs (bp) and scaffolds with a depth value lower than 25% of the mean depth were removed.…”
Section: Methodsmentioning
confidence: 99%